Kansas State University: From Black Athlete to Black Student Union - Walpool, Ti'Ara (Kansas State University, The Chapman Center for Rural Studies, 2009)
This paper explores the history of Kansas State University's Black Student Union, which was founded in 1968 by black K-State athletes as a site of solidarity in a time of social upheaval and racial progress. The author analyzes the founding of the BSU as part of the history of African American athletes claiming space for themselves in white-dominated organizations.
Ti'Ara Walpool, “Kansas State University: From Black Athlete to Black Student Union,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/231.
Keywords: African American history; African Americans; Black Student Union; Kansas State University; Riley County; sports